Android boot camp for developers using Java(TM), comprehensive : - Hoisington, Corinne (Course Technology Cengage Learning, 2013)
This book prepares readers with a thorough introduction to both Java™ and the secrets to creating effective mobile applications. It's the ideal choice for readers who already have a little programming experience or are new to Java. The book offers a hands-on tutorial approach with clear, step-by-step instruction and numerous screen shots to guide readers through tasks efficiently. Learners gain a solid understanding of programming logic and Java tools for Android today and into the future.